Роль світла в архітектурі громадських будівель. футуристичний аспект - Яців, С. М.; Яців, М. Б.; Yatsiv, S. M.; Yatsiv, M. B. (Видавництво Львівської політехніки, 2018)
Досягнення сучасної архітектури не зменшили, а навпаки, розширили функції світла у формуванні простору й архітектоніки громадських будівель. Архітектурний простір пропонує нові рішення, тектоніка будівлі – нові форми відповідно до тенденцій в архітектурі та дизайнерських ідей. На підставі аналізу формування світлового середовища в просторі сучаснихгромадськихбудівель здійснено спробу спрогнозувати напрям, характер і особливості функціонування світла в архітектурі окремих типів громадськихбудівель.

In the article the tendencies of use of natural light in modern buildings of culture and churches are considered. Buildings of culture have always been special objects of experimentation with light. In the historical monumental and chamber sacral buildings, the way of using light almost did not change for centuries. Light in the space of cultural buildings.In cultural buildings, natural light is not necessary for utilitarian needs, and sometimes even undesirable. For example, in theater buildings, museums, in objects intended for performing arts, etc. His utilitarian role is minimal, and the desired comfort of visual perception is achieved by means of artificial lighting. The original prototypes of modern public buildings have been realized in the middle of the last century: the Museum of the Guggenheim in New York (1959), the Chapel in Ronchamp (1955), the Opera House in Sydney (1959–1979) and Berlin National Gallery (1968).The house-icon, which significantly influenced the architecture of modern cultural buildings, and led to the rejection of many stereotypes, became the Museum of the Guggenheim in Bilbao (1997). Determined types of buildings in which light penetrates differently. In some, natural light is an important form-forming element of the structure. For example, in the Museum of the Guggenheim in New York and the Museum of Contemporary Art in San Francisco, the spatial structure of buildings is formed around a pillar of light that penetrates the buildings from the top to the bottom. There are also cultural objects in which natural light penetrates inside from all sides, due to the use of frame structures. Among the first we note the project of the New National Gallery of Berlin. The light literally penetrates the exhibition space of the main hall, through the glass walls. In many modern buildings of culture, through the transparent facades, only the expanses of the foyer, vertical communications, and curbs are lit. Instead, the main rooms are closed to daylight. Light in the sacred space of the temple. Today, in the world practice of building temples, three main trends have been identified. Much of the contemporary realized sacred objects with its architectonics and the degree of interference of natural light in the interior space testifies to their significant isolation from the environment. Others allow light to be dosed, usually covering the main spaces and fragments of the sacred space. The third group consists of buildings that are completely open outside to the environment, combining the whole interior and exterior space. In many modern monumental and minimalist temples, the interior space of which is devoid of architectural details, which often cause a feeling of emptiness, the only creator of sacredness is the natural light. For example, in the Chapel of Brother Claus (architect P. Zumthor) end in the Temple of Light (architect T. Ando). Other values of light were declared by artists of the near past, for which the space of architecture is the ratio of abstract concepts. The avant-garde world of art, starting with the principles of Le Corbusier, interprets the light in a new way. The light in such temples is a universal means for identifying the function of the architectural space, a factor that provides an atmosphere of concentration of attention and meditation, suitable for contemplation and prayer. The article also discusses some aspects of the use of artificial light. It is established that natural light is gradually replaced by artificial light, first in the form of electric lighting, then in the form of light technologies that create a new reality
Role of light in the architecture of public buildings. futuristic aspect
Keywords: : будівлі культури; сакральні будівлі; природне і штучне світло; середовище; простір; environment; space; natural and artificial light; sacred buildings; buildings of culture; 725.8.01; 726.5